Answer:
Step-by-step explanation:
He has owned a dog for 9 years, and this time is one year less than twice as long as he has owned a cat.
So, we can express this like:
Solving for :
Therefore, he has owned a cat for 5 years.
12(b+2)+3b=−1
Enter your answer as a fraction.
The solution to the equation 12(b+2) + 3b = -1 is b = -5/3.
Given the equation in the question:
12( b + 2 ) + 3b = -1
To solve the equation 12( b + 2 ) + 3b = -1, first apply the distributive property.
Distribute the 12 across the terms inside the parentheses:
12( b + 2 ) + 3b = -1
12×b + 12×2 + 3b = -1
Simplifying, we get:
12b + 24 + 3b = -1
Collect and combine the like terms on the left side of the equation:
12b + 3b + 24 = -1
15b + 24 = -1
Subtract 24 from both sides of the equation:
15b + 24 - 24 = -1 - 24
15b = -1 - 24
15b = -25
Divide both sides by 15:
b = -25/15
Simplify
b = -5/3
Therefore, the value of b is -5/3.
Learn more about equations here: brainly.com/question/14686792
#SPJ2
Answer: -5/3
Step-by-step explanation:
12(b + 2) + 3b = -1
12b + 24 + 3b = -1
15b + 24 = -1
15b = -1-24
b = -25/15 = -5/3
Please help me! This is kind of confusing, and I don't really understand.
Answer:
2 and 3
Step-by-step explanation:
9/4=2.25